2022
DOI: 10.1088/1755-1315/1007/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the effect of home appliances use to electricity consumption during WFH

Abstract: Various forms of quarantine and social restrictions to prevent the spread of the COVID-19 pandemic has impacted lifestyle. WFH has emerged as a growing trend in this new normal era. The implementation of WFH results in all work-related activities becoming home-centred. This study aims to analyse the pheasant and find out the effect of household appliance use on energy consumption during the implementation of WFH. The questionnaire survey was conducted in April 2020 and it collected 215 responses from residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The extensive coverage of impermeable surfaces in urban areas leads to increased absorption of solar heat and the reflection of heat and combustion gases produced by urban activities and the growing number of private vehicles, exacerbating UHI conditions [6]. These effects have significant impacts on air quality, human health, energy consumption in cities, and contribute to extreme global warming in Indonesia [7]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…The extensive coverage of impermeable surfaces in urban areas leads to increased absorption of solar heat and the reflection of heat and combustion gases produced by urban activities and the growing number of private vehicles, exacerbating UHI conditions [6]. These effects have significant impacts on air quality, human health, energy consumption in cities, and contribute to extreme global warming in Indonesia [7]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in electricity and gas consumption due to the longer time spent at home during WFH needs to be underlined ( Novianto et al, 2021b , Gao and Novianto, 2018 ). Some research found that the length of WFH time during the pandemic lockdown affected an increase in energy consumption, especially from the use of a home computer, internet, rice cooker, AC, and water needs in a household ( Hutama et al, 2022 ). Further, AC is a factor that has a significant negative effect on the increase in household electricity consumption during the pandemic ( Novianto et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%